2001
DOI: 10.1128/jcm.39.11.4013-4019.2001
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Flagellin A Proteins from Borrelia burgdorferi Sensu Stricto, B . afzelii , and B. garinii in Serodiagnosis of Lyme Borreliosis

Abstract: Genes for flagellin A (FlaA) proteins from European borrelial strains of Borrelia burgdorferi sensu stricto, B. afzelii, and B. garinii were cloned and sequenced. An identity of 92 to 93% was observed in the flaA sequences of the different species. Polyhistidine-tagged recombinant FlaA (rFlaA) proteins were produced in Escherichia coli and used as antigens in Western blotting (WB) and enzyme-linked immunosorbent assay (ELISA). In immunoglobulin G (IgG) WB, 71% (10 of 14) of the sera from neuroborreliosis and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
(17 reference statements)
1
14
0
2
Order By: Relevance
“…In an early exposure to borreliae, the expected IgM isotype antibodies could be detected only infrequently. The reason for this is unknown, but the low sensitivity of IgM serology has also been associated with most of the other new recombinant borrelial antigens tested (17,20,21,24). Hence, the present results imply that assessments for IgG antibodies, although not IgM antibodies, to BBK32 proteins may afford a major improvement in the serodiagnosis of early LB.…”
Section: Discussionmentioning
confidence: 74%
“…In an early exposure to borreliae, the expected IgM isotype antibodies could be detected only infrequently. The reason for this is unknown, but the low sensitivity of IgM serology has also been associated with most of the other new recombinant borrelial antigens tested (17,20,21,24). Hence, the present results imply that assessments for IgG antibodies, although not IgM antibodies, to BBK32 proteins may afford a major improvement in the serodiagnosis of early LB.…”
Section: Discussionmentioning
confidence: 74%
“…BdrT, also called BdrF2, has been reported to be upregulated in "host-adapted" B. burgdorferi and to be specifically expressed during early infection in mice (75,97). This study revealed that several flagellar apparatus proteins besides FlaB flagellin (BB0147), the FlgE hook protein (BB0283), and the FlaA protein (BB0668) (42,51,69,77) elicit antibody responses during infection. Brinkmann et al found that FlgE of T. pallidum was frequently bound by antibodies in sera from patients with syphilis (11).…”
Section: Discussionmentioning
confidence: 98%
“…The internal portion of the flagellin molecule, containing the variable, genus-specific immunodominant domain, is less cross-reactive with antigens of other bacteria than the whole protein (101,179,274). The flagellar outer sheath protein FlaA, with a molecular size of 37 kDa, is another immunodominant antigen, especially in early disease (7,84,104,246).…”
Section: Immunologic Diagnosis Of B Burgdorferi Sensu Lato Infectionmentioning
confidence: 99%